Democratization and women's grassroots movements - Bystydzienski, Jill M.; Sekhon, Joti (Indiana University Press, 1999)
The essays in this volume map the concerns of gender onto the terrain of nation, finding significant connections, disjunctions, and tensions between them. The authors argue that for any cultural analysis to be performed in the context of the decolonized nation-space, gender must take centrestage. The essays explore gender as a point of crisis in the cultural, social and political space of a nation. They attribute the existence of these crises to conflicts between gender, on the one hand, and family, community and nation on the other. These are then analysed in terms of female identity, subjectivity and agency within a narrative of historical modernity.